2022
DOI: 10.1155/2022/9882113
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of MOOC System for English Intercultural Communication Courses Using Neural Network

Abstract: Presently, many researchers are focusing on the English intercultural communication course. However, these courses face serious challenges, such as individual student variances in conventional English cross-cultural teaching, fostering students’ cross-cultural communication abilities, and enhancing teaching quality. These problems need to be solved; therefore, this paper aims to explore the development and application of the Massive open online courses (MOOCs) system in the English cross-cultural communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The experimental result of proposed MOOCEC-HDNN method is discussed in this section.. Then, proposed technique is simulated utilizing Python under several performance metrics. The obtained outcomes of proposed MOOCEC-HDNN are compared with existing MOOCEC-CNN [21], MOOCEC-GA-NN [22] and MOOCEC-KMA-NN [23] models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental result of proposed MOOCEC-HDNN method is discussed in this section.. Then, proposed technique is simulated utilizing Python under several performance metrics. The obtained outcomes of proposed MOOCEC-HDNN are compared with existing MOOCEC-CNN [21], MOOCEC-GA-NN [22] and MOOCEC-KMA-NN [23] models.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang and Hou [21] have suggested to discover the application and growth of the neural network-based MOOCs system for the English course on cross-cultural communication. First, the general function components of the MOOC system were explained; with a focus on the system database design, student function module, administrator function module, and teacher functional module, for EICC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were proposed in the literature concerning the international students intercultural adaptation; this review covers a few current works, Jiang and Hou [21] have suggested that creation and implementation of a neural network-based vast system of open online courses for English-language intercultural communication courses. to investigate the enlargement and implementation of the MOOCs platform in the English neural network course-based cross-cultural communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The intercultural teaching activities in online classrooms open up a window for students to know about the world, so that they can view and treat different cultures and ideas with an open mind [11,12]. The intercultural exchanges can not only drive the personal growth of students, but also build a bridge for international educational cooperation and cultural exchange [13][14][15]. Systematically researching the intercultural teaching activities using scientific methods such as data mining can provide data evidences for educational administrators and decision makers, so that more accurate and efficient teaching activities can be designed and implemented [16,17].…”
Section: Introductionmentioning
confidence: 99%